2001
DOI: 10.1089/08892220150217201
|View full text |Cite
|
Sign up to set email alerts
|

Closely Related HIV-1 CRF01_AE Variant among Injecting Drug Users in Northern Vietnam: Evidence of HIV Spread across the Vietnam–China Border

Abstract: To investigate the nature of recent HIV outbreaks among injecting drug users (IDUs) near the Vietnam-China border, we genetically analyzed 24 HIV-positive blood specimens from 2 northern provinces of Vietnam (Lang Son and quang Ninh) adjacent to the China border, where HIV outbreaks among IDUs were first detected in late 1996. Genetic subtyping based on gag (p17) and env (C2/V3) sequences revealed that CRF01_AE is a principal strain circulating throughout Vietnam, including the provinces near the China border.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
19
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 16 publications
4
19
1
Order By: Relevance
“…By 1995, CRF01_AE was widespread among Thai IDUs (20,56), and IDU populations in other countries, such as Vietnam and Malaysia, had experienced rapid increases in CRF01_AE infections (21,43,46). In 1996 and 1997, an outbreak of CRF01_AE, genetically highly similar to the Vietnamese strain, was detected among IDUs in China (22). Today, the HIV-1 epidemic in South and Southeastern Asia is complicated not only by the interplay of injecting drug use and commercial sex work but also by the circulation of numerous HIV-1 subtypes in these risk groups, resulting in the emergence of novel intersubtype and unique recombinant strains (57,62).…”
mentioning
confidence: 99%
“…By 1995, CRF01_AE was widespread among Thai IDUs (20,56), and IDU populations in other countries, such as Vietnam and Malaysia, had experienced rapid increases in CRF01_AE infections (21,43,46). In 1996 and 1997, an outbreak of CRF01_AE, genetically highly similar to the Vietnamese strain, was detected among IDUs in China (22). Today, the HIV-1 epidemic in South and Southeastern Asia is complicated not only by the interplay of injecting drug use and commercial sex work but also by the circulation of numerous HIV-1 subtypes in these risk groups, resulting in the emergence of novel intersubtype and unique recombinant strains (57,62).…”
mentioning
confidence: 99%
“…32 This has also been observed in the context of CRF01_AE in northern Vietnam and Southern China since the 1990s to more recently. 5,6,21,30 The analysis of synonymous and nonsynonymous nucleotide changes indicated that the maternal sequences had evolved when comparing them to the older sequences from northern Vietnam. It was not possible to discern whether HIV-1 in pregnant women has evolved as a result of spreading into the general population, or is still closely related to the epidemic among intravenous drug users, a group that dominates as a source of HIV sequences in this part of the country.…”
Section: Hiv-1 Env Sequences In Pregnant Women In Vietnamcan Be Identmentioning
confidence: 99%
“…However, the topology of the tree was similar to a recently reported phylogenetic analysis of the spread of HIV-1 CRF01_AE from Thailand to Southern Vietnam and then to the North. 28 The closest relationships between the sequences from northern Vietnam and a foreign source was found with the HIV-1 Pingxiang strains of HIV-1-infected individuals from the Guangxi province 5,6 in southern China, which borders with the Lang Son province in northern Vietnam.…”
mentioning
confidence: 94%
See 2 more Smart Citations